Development of a fluorescence resonance energy transfer (FRET)-based DNA biosensor for detection of synthetic oligonucleotide of Ganoderma boninense - Mohd Bakhori, Noremylia; Yusof, Nor Azah; Abdullah, Abdul Halim; Hussein, Mohd Zobir (MDPI, 2013)
An optical DNA biosensor based on fluorescence resonance energy transfer (FRET) utilizing synthesized quantum dot (QD) has been developed for the detection of specific-sequence of DNA for Ganoderma boninense, an oil palm pathogen. Modified QD that contained carboxylic groups was conjugated with a single-stranded DNA probe (ssDNA) via amide-linkage. Hybridization of the target DNA with conjugated QD-ssDNA and reporter probe labeled with Cy5 allows for the detection of related synthetic DNA sequence of Ganoderma boninense gene based on FRET signals. Detection of FRET emission before and after hybridization was confirmed through the capability of the system to produce FRET at 680 nm for hybridized sandwich with complementary target DNA. No FRET emission was observed for non-complementary system. Hybridization time, temperature and effect of different concentration of target DNA were studied in order to optimize the developed system. The developed biosensor has shown high sensitivity with detection limit of 3.55 × 10−9 M. TEM results show that the particle size of QD varies in the range between 5 to 8 nm after ligand modification and conjugation with ssDNA. This approach is capable of providing a simple, rapid and sensitive method for detection of related synthetic DNA sequence of Ganoderma boninense.